Efektivitas Aplikasi Mobile JKN Dalam Meningkatkan Pelayanan BPJS Kesehatan di Rumah Sakit Islam Malahayati Medan - Budiarti, Tri (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
ABSTRACT The problem currently in society is that not many people know and do not understand how to use the JKN Mobile Application. This research aims to determine the effectiveness of the JKN Mobile Application in Improving BPJS Health Services, and what factors hinder the JKN mobile application in improving BPJS Health services. The method in this research is a descriptive qualitative method and data collection techniques through observation, interviews and documentation. This research was carried out in April-May 2024 at the Malahayati Islamic Hospital, Medan. The results of this research show that the effectiveness of the JKN Mobile Application in Improving BPJS Health Services at the Malahayati Islamic Hospital in Medan can be seen as not being effective from the indicators of program understanding, targets, time and achievement of goals. Several things that are obstacles to the effectiveness of the JKN Mobile Application in improving BPJS Health services at the Malahayati Islamic Hospital in Medan are a lack of knowledge which causes misunderstanding and the public does not understand the use of the JKN Mobile Application. Keywords: Effectiveness, Mobile Application, BPJS Health Services